STUDY OF LITERATURE THE LEVEL OF CRITICAL THINKING ABILITY OF STUDENTS RELATED TO MATHEMATICS MATERIALS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The purpose of this paper is to discuss the level of students' critical thinking skills in solving problems related to the topic or subject matter of Mathematics. To achieve this goal, the method used is literature study by describing the ability to think critically based on several experts and describe the leveling of critical thinking based on the study of supporting references. In everyday life, one cannot escape thinking. One of the thinking activities needed in life is critical thinking. The development of critical thinking skills can be done through school, which is one of them in the Mathematics learning process. Giving problem solving can help students develop critical thinking skills. But in the development of critical thinking processes, even though students receive the same material and the learning process, it does not rule out the possibility that there are differences in the ability to think critically in each student. Differences in the ability to think critically in students can be revealed by making groups based on certain criteria so that the level of critical thinking skills of students from highest to lowest can be seen.